2022
DOI: 10.3390/s22020453
|View full text |Cite
|
Sign up to set email alerts
|

Markerless Image Alignment Method for Pressure-Sensitive Paint Image

Abstract: We propose a markerless image alignment method for pressure-sensitive paint measurement data replacing the time-consuming conventional alignment method in which the black markers are placed on the model and are detected manually. In the proposed method, feature points are detected by a boundary detection method, in which the PSP boundary is detected using the Moore-Neighbor tracing algorithm. The performance of the proposed method is compared with the conventional method based on black markers, the difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…As preprocessing, flood filling ( Figure 18 c) and image rotation ( Figure 18 d) were applied [ 6 ], after iterative binarization ( Figure 18 b) of the grayscale image ( Figure 18 a). For an objective performance analysis, the performance of the proposed method was compared with those of the line-based [ 7 , 14 ] and corner-based reference point extraction methods [ 8 , 9 , 14 ], among the existing reference point search algorithms [ 8 , 9 , 14 ].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…As preprocessing, flood filling ( Figure 18 c) and image rotation ( Figure 18 d) were applied [ 6 ], after iterative binarization ( Figure 18 b) of the grayscale image ( Figure 18 a). For an objective performance analysis, the performance of the proposed method was compared with those of the line-based [ 7 , 14 ] and corner-based reference point extraction methods [ 8 , 9 , 14 ], among the existing reference point search algorithms [ 8 , 9 , 14 ].…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Thereby, the correspondence between the key points in the two images is established. Suzuki et al [10] proposed a markerless registration method using the Moore-Neighbor tracking algorithm to detect the boundary of the PSP and using boundary points as feature points. Experiments showed that this method has a lower computational cost than the difference-of-Gaussian detector [7] while maintaining good registration accuracy.…”
Section: Introductionmentioning
confidence: 99%